O conflito entre o público e o privado: as enfermidades do sistema e a judicialização da saúde no Estado do Tocantins - Raddatz, Lucimara Andreia Moreira (Universidade Federal do Tocantins, 2016)
Despite the major institutional changes concerning the right to health in Brazil, the implementation of public policies capable of effecting full access, universal and equal or all, in the Federal Constitution in 1988, has not been priority of managers, showing encourage access by private road, also leaving fulfill its obligations. In this technical report, by analyzing critical sought to highlight the contradiction, to acquire greater clarity or the conflict between public and private, considering how assumptions: 1) that the deterioration of public health comes from the expansion of the privatized market; 2) that the party fails private has its foundations stuck in a contract for- profit and cot care full of customers, disregarding the legally established. In either case, public and private have something in common: disrespect to citizen. This fact triggers a series of demands on the judiciary, whose purpose is to have guaranteed constitutionally entrenched right. Lawsuits were examined about right to health in the State of Tocantins, as well as instruments that identified to establish greater effectiveness in adjudication, the main shed the realization of the right to health by citizens. To this end, we carried out a research that aimed to analyze 704(seven hundred and four) legal proceedings, divided into fourteen (14) different subtypes classified as potentially on the topic, distributed in the District of Palmas in 2014, quantifying , typifying and analyzing them as a series of decisions. Refined research, the processes that did not concern the right to health were excluded, the processes sensitive and rogatory letters, leaving 236(two hundred thirty-six), whose main elections are performing surgeries, provision of medicines and treatments specialized. The analysis of these requirements by the judiciary depends on support area of technical oblivious to the attention of judges in order to provide a grant for decisions and also swiftly as health problems demand. For this reason was established the Technical Support Unit (NAT). However, it was observed that in the year 2014 in Palmas were seconded NAT only 25 reports by the judiciary in average two requests per month. Does NAT is being underused? Because a reduced number of was ordered? The problem evidenced by the analysis of the process was the characterization of bond with one of the parties involved in process, since NAT is linked to the state of Tocantins, the main defendant in process. In this sense, the hypothesis put forward is that the NAT may be compromising the objectivity of opinion by way of subsidy to judicial decisions. Having in view its link with the Health Secretariat of the State(SESAU), it was conclude that there is a need to recast the Center for Technical Support (NAT), making it linked to the Court of Justice of the State of Tocantins. The objective of this technical report is to provide information that demonstrates the problem and the reasons for its recast proposal. Therefore, a proposal is attached to the report.